How effective are labor wages on labor productivity?: An empirical investigation on the construction industry of New Zealand - Ozturk, Mustafa; Durdyev, Serdar; Aras, Osman Nuri; Ismail, Syuhaida; Banaitienė, Nerija (Technological and Economic Development of Economy, 2020)
This study empirically investigates (for the period of 1983–2017) the relationships between the parameters (labour wage (LW), labour productivity (LP) and unemployment (UNM) rate) of the construction sector in New Zealand. This study employs the Johansen co-integration test to determine if the relationship in the long run does exist among the investigated variables as well as to assess the relationships. The results show that the LW has a positive effect on the LP, while the UNM affects negatively, which indicates that the higher salary, the more productive labour. In other words, increase in salary stimulates the belief of the workforce that they are substantially paid for their work, which ultimately increases their trust and loyalty to the employer; hence, productivity. Moreover, the results show adverse effect of UNM on LP, which indicates that labours may also lose his/her productivity due to fear of losing his/her job. The model stability is verified by Histogram Normality Test, Breusch-Godfrey Serial Correlation, Heteroscedasticity Breusch-Pagan-Godfrey tests. Thus, the forefront of the construction sector is recommended to consider the empirical relationships determined in this study in order to improve the productivity level at various levels.